2006
DOI: 10.1080/09297040500473714
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Mullen Scales of Early Learning for the Assessment of Young Children with Autism Spectrum Disorders

Abstract: The psychological assessment is an important component of the diagnostic evaluation in young children suspected of having an autism spectrum disorder but can be hampered by behavioral difficulties. Overt behaviors during administration of the Mullen Scales of Early Learning were coded in 22 preschoolers with an autism spectrum disorder and 20 age-matched typically developing children. Children in the autism spectrum disorder group required less time to complete the assessment but spent proportionally more time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
138
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(140 citation statements)
references
References 26 publications
0
138
1
1
Order By: Relevance
“…It can be used with older children as in the present study where mental age is lower than chronological age. This measure was used to assess a range of skills in children with autism in previous research [25,[35][36][37]. Age-equivalent scores were used in the analyses as some children's chronological age exceeded 68 months at post (Time 2) assessment; additionally many children did not reach the basal for standard scores.…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…It can be used with older children as in the present study where mental age is lower than chronological age. This measure was used to assess a range of skills in children with autism in previous research [25,[35][36][37]. Age-equivalent scores were used in the analyses as some children's chronological age exceeded 68 months at post (Time 2) assessment; additionally many children did not reach the basal for standard scores.…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…Each subscale yields developmental age equivalents, and thus is applicable to developmentally delayed children outside the 68-month normed age range [46]. The Mullen shows good test-retest and inter-rater reliability [47] and strong concurrent validity with other developmental tests of motor and language skills, including the VABS [45].…”
Section: ) Outcome Measures -Externalmentioning
confidence: 99%
“…These external, psychometric measures are analysed via a 2x2 (motor-impaired or motorintact subgroup, Point OutWords treatment or iPad control condition) repeated-measures analysis of variance. The Mullen Scales of Early Learning are widely used to measure cognitive and language skills in research and clinical evaluations of autistic children [44,45]. Each subscale yields developmental age equivalents, and thus is applicable to developmentally delayed children outside the 68-month normed age range [46].…”
Section: ) Outcome Measures -Externalmentioning
confidence: 99%
“…The participants were not matched by age; consequently, it was difficult to compare one participant to the other in terms of where they land developmentally. Additionally, Munson et al (2008) found that floor scores on the Mullen Scales of Early Learning are extremely common within the autism population and Akshoomoff (2006) stated that it is difficult to interpret T-scores that fall at or below 20, leaving us with little information regarding how the six participants in the current study truly differed in their skill level.…”
Section: Future Directionsmentioning
confidence: 97%